Transformative Stories: A Framework for Crafting Stories for Social Impact Organizations. (September 2016) - Bublitz, Melissa G.; Escalas, Jennifer Edson; Peracchio, Laura A.; Furchheim, Pia; Grau, Stacy Landreth; Hamby, Anne; Kay, Mark J.; Mulder, Mark R.; Scott, Andrea
This article provides a framework to guide the construction of transformative stories by social impact organizations (SIOs) including nonprofit organizations, public policy entities, and for-profit social benefit enterprises. This framework is built from the integration of the academic literature on narratives and narrative construction relevant to SIO story construction. This transformative story construction framework outlines how SIOs can assemble and craft authentic and effective stories that convey the organization's impact, engage audiences, and call those audiences to action as well as how SIOs can develop and manage a portfolio of such stories. The framework also provides recommendations to guide the marketplace practice of transformative story construction by SIOs. Finally, the authors pose questions to engage SIOs in collaborative research to refine the practice of constructing stories with the power to transform.